Extracranial complications after traumatic brain injury: targeting the brain and the body. Issue 2 (April 2020) - Robba, Chiara; Bonatti, Giulia; Pelosi, Paolo; Citerio, Giuseppe
Abstract : Purpose of review: The aim of this review is to provide an update on the pathophysiology and treatment of severe traumatic brain injury (TBI)-related complications on extracranial organs. Recent findings: Extracranial complications are common and influence the outcome from TBI. Significant improvements in outcome in a sizeable proportion of patients could potentially be accomplished by improving the ability to prevent or reverse nonneurological complications such as pneumonia, cardiac and kidney failure. Prompt recognition and treatment of systemic complications is therefore fundamental to care of this patient cohort. However, the role of extracranial pathology often has been underestimated in outcome assessment since most clinicians focus mainly on intracranial lesions and injury rather than consider the systemic effects of TBI. Summary: Robust evidence about pathophysiology and treatment of extracranial complications in TBI are lacking. Further studies are warranted to precisely understand and manage the multisystem response of the body after TBI.